Is Anticoagulation Discontinuation Achievable with Citrate Dialysate during HDF Sessions?. (10th October 2016) - Dolley-Hitze, Thibault; Oger, Emmanuel; Hamel, Didier; Lombart, Marie-Laure; Hermès, Isabelle
Abstract : Citrate dialysate has been developed for few years to replace acetate and HCl concentrates. In Online Postdilution Hemodiafiltration (OL-POST-HDF), several issues are remaining concerning the possibility of stopping anticoagulation during sessions and the side effects of citrate solutions on calcium metabolism. This 1-year monocentric retrospective study included all patients exposed to citrate in OL-POST-HDF with nadroparin decrease for more than one month. Clotting events, serum calcium, PTH, hemoglobin, CRP, depuration parameters, and treatments administrated were recorded for analysis. 27 patients experienced nadroparin decrease and 5 did not receive nadroparin at the end of the study. Nadroparin decrease and withdrawal were both associated with more clotting events whereas the use of vitamin K antagonists was protective. No significant metabolic side effects were observed. Citrate dialysate does not allow anticoagulation discontinuation or decrease but has no significant side effects on mineral bone metabolism or erythropoiesis.